IPTEKS BAGI MASYARAKAT KELOMPOK USAHA PETANI KELAPA DESA SEI PAHAM - La Ane; Muhammad Bukhori Dalimunthe (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
The purpose of IbM to utilize the coconut husk waste in order to be fully utilized for productive activitiesthat can develop communities economically independent and improve skills in processing waste coconuthusks into craft items. The method used to achieve IbM activity is a method of education, counseling,training, production, business management training, design,  and mentoring. This work was conducted atthe home partner named Japilian Dalimunthe address Sei Sei Understanding Middle Kepayang shavingsDistrict is approximately 220 km from the State University of Medan . Result of performance of activitiesIbM broadly divided into, namely : ( 1 ) soft skills, provision of education and counseling utilization of wasteoil into the craft mat and strap goods that have economic value ; and ( 2 ) hard skills , training, and practicemat production and rope directly involve partners and communities as well as the evaluation of the matand rope production. So also with the additional income earned for production partners mat and strap anda positive impact on the reduction of waste coconut husks piled in the garden or in the yard partner..